ChatGPT 5.5 as an Automated Corrective Feedback Tool: Effects on the Writing Performance of EFL Learners - Abdullah Al Maqbali; Olga Taga (Language, Technology, and Social Media, 2026)
The present paper focused on examining the application of GPT‑5.5 as an automated corrective feedback tool for improving the writing skills of 60 Omani pre‑intermediate EFL students enrolled in a foundation program. A quasi‑experimental pretest–posttest design was used, and the participants were divided into two groups, namely an experimental group and a control group, each receiving instruction on advantages‑and‑disadvantages essays. While both groups followed the same syllabus and classroom procedures, only the experimental group utilized GPT‑5.5 AI tool for iterative feedback and revision, supplemented by teacher explanation and clarification. The analytic scoring of the pretest and posttest compositions demonstrated that both groups made progress, yet the experimental group scored substantially better on the posttest, with a large effect size. The results imply that the use of AI‑mediated feedback, when systematically integrated with teacher support, can be an effective and scalable way to advance EFL learners’ writing skills in similar contexts.